Monitoring consumer responses to online advertising via neuro-marketing techniques: an exploratory study (European journal of volunteering and community-based projects, 2023)
Neuromarketing is a widespread research methodology in marketing, and nowadays is being employed also for the assessment of digital communication: however, no experimental research has been conducted on a website banner. This paper assesses the effects of this kind of digital stimuli on the consumer audience by using neuro-marketing techniques. Specifically, the research aims to verify consumers’ responses to a website banner in terms of attention, cognitive effort, interest and emotion by carrying on an exploratory experiment on a pilot sample of Italian consumers. The study was approached in four stages. In the first step, a selected brand has been analysed as a case study in an industry that has only recently entered the digital touchpoint; in the second step, a digital stimulus has been selected; in the third step, an experimental protocol was developed and tested; finally, the above-mentioned neuro-marketing experiment has been carried out. Results show that the effectiveness of the banner is linked to its position on the web page, but this is not enough: for better effectiveness, it has also to be framed properly in the website navigation design.